Theories of Value and the Monetary Theory of Production - L. Randall Wray (Levy Economics Institute of Bard College, 1999)
This paper extends earlier work that argued that liquidity preference theory should be interpreted as a theory of value. Here I will argue that two theories of value are needed for analysis of a monetary production economy: the labor theory of value and the liquidity preference theory of value. Both Keynes and Marx were trying to develop a monetary theory of production; Marx, of course, adopted a labor theory of value in his analysis, and it was previously argued that Keynes adopted a liquidity preference theory in his. A monetary theory of production should adopt both, however, and I will argue that Keynes seems to have recognized this. Further, Keynes did adopt labor hours as the measure of value and said he agreed that labor produces all value. I admit it is still a leap to claim that Keynes accepted both theories of value. Instead, I argue he should have adopted both and will show that this is consistent with the purposes of the General Theory.
Keywords: 330